Neurocognitive function influences dynamic postural stability strategies in healthy collegiate athletes. Issue 1 (January 2022) - Porter, Ke'La H.; Quintana, Carolina; Morelli, Nathan; Heebner, Nicholas; Winters, Joshua; Han, Dong Y.; Hoch, Matthew
Abstract: Objectives: Poorer neurocognitive performance may increase lower extremity injury risk due to alterations in biomechanics. However, it is unclear if poorer neurocognitive function may be associated with altered dynamic postural stability. Therefore, the purpose of this study was to investigate the relationship between neurocognitive performance and dynamic postural stability in healthy collegiate athletes. Design: Cross-sectional cohort. Methods: Forty-five Division-I collegiate athletes (21 males, 24 females; age: 19.69 ± 1.50) completed neurocognitive assessments from the NIH Toolbox® (NIHTB). Three groups were established from the NIHTB composite score: high performers (HP), moderate performers (MP), and low performers (LP). Additionally, participants completed a dynamic hop-to-stabilization task. Accelerometer and gyroscopic data were recorded during landing through an inertial measurement unit (IMU) on the participant's low back. The root mean squared (RMS) of the accelerometer and gyroscope was calculated for the orthogonal planes and the resultant vector. Group differences for demographic variables, NIHTB composite scores, and IMU based measures were analyzed with one-way ANOVAs with Bonferroni post hoc analyses were performed. Cohen's d effect sizes were also calculated. Results: Post hoc tests determined the LP group had higher vertical acceleration RMS values ( p = 0.013, d = −0.85) and lower anteroposterior acceleration RMS values ( p = 0.005, d = 0.95) compared to the HP group. Conclusions: Neurocognitive performance may influence dynamic postural stability strategies in athletes. Higher neurocognitive performers may use different approaches to perform difficult postural tasks by adopting strategies associated with lower vertical and higher anteroposterior acceleration compared to lower neurocognitive performers.